Exploring the relationships between collective efficacy, perceptions of success, and team attributions - Chow, G. M.; Feltz, D. L. (Journal of Sports Sciences, 2008)
We examined the influence of collective efficacy and subjective interpretations of success/failure on team causal attributions. The participants were 71 male and female high school athletes on 20 track relay teams. Before a selected competition, participants completed a collective efficacy questionnaire. Then, immediately after their race, they were administered a modified version of the revised Causal Dimension Scale-II. A multi-level framework was employed to assess collective efficacy as an individually held perception and as a shared team belief. The individual perceptions of team success/failure significantly predicted the locus of causality and stability dimensions, whereas aggregated collective efficacy emerged as a significant team level predictor of average stability. Individual perceptions of collective efficacy were significantly related to team control and this relationship was moderated by the sex of the team. The findings indicate that collective efficacy beliefs held by athletes and teams prior to a competition influence the formation of post-competition team attributions in sport.